2020
DOI: 10.5334/irsp.291
|View full text |Cite
|
Sign up to set email alerts
|

Nationalistic Collective Rituals, Intergroup Relations, and Legitimation of National Social Systems

Abstract: It was as if we had beaten a country, not just a football team… Although we had said before the game that football had nothing to do with the Malvinas war, we knew they had killed a lot of Argentine boys there, killed them like little birds. And this was revenge. (Diego Maradona, 2007) I hope that people can understand that football is a sport, not war […] The past is the past. We must not put sport in the middle of politics. Chile and Argentina are brother countries, we have to show mutual respect […] If we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…This theorization explains why our results show the social effects on the fans’ trust in the categorized people within the social group “my country,” unlike what happens in other non-competitive collective rituals that favors prosocial behavior toward conspecifics and non-conspecifics. Furthermore, as previous studies related to major sport events and other types of collective rituals had pointed out, in our study, we were able to observe a clear effect on the well-being of those people who actively participated in these events ( Páez et al, 2015 ; Unanue et al, 2020 ; Vargas-Salfate et al, 2020 ). This goes in line with social identity researchers that highlight the effects that a shared social identity and the sense of “we-ness” have on health and well-being ( Khan et al, 2015b ).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This theorization explains why our results show the social effects on the fans’ trust in the categorized people within the social group “my country,” unlike what happens in other non-competitive collective rituals that favors prosocial behavior toward conspecifics and non-conspecifics. Furthermore, as previous studies related to major sport events and other types of collective rituals had pointed out, in our study, we were able to observe a clear effect on the well-being of those people who actively participated in these events ( Páez et al, 2015 ; Unanue et al, 2020 ; Vargas-Salfate et al, 2020 ). This goes in line with social identity researchers that highlight the effects that a shared social identity and the sense of “we-ness” have on health and well-being ( Khan et al, 2015b ).…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, data from a recent study conducted by Vargas-Salfate et al (2020) show that sports macro-events can favor the self-affirmation of the group, especially when victory occurs, but this does not necessarily lead to out-group derogation. In this way, although in-group identity does not imply out-group hate, when this identification with the group becomes dominant, hostility and fear within the in-group will appear, especially in a context of scarce resources and feelings of fear generated by out-group hostility ( Brewer, 2001 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, desecration of both an ingroup and an outgroup symbol can be considered an act of deviance, varying in degree depending on the emphasis placed on either the norm of loyalty or of nonaggression of outgroups, respectively. In a context where the norm of group loyalty and symbols are particularly valued (i.e., a context of sports competition; see Travaglino et al, 2014;Vargas-Salfate et al, 2020;von Scheve et al, 2014), being faced with an ingroup (vs. outgroup) flag being burnt by ingroup perpetrators causes an increase in ingroup bias among other ingroup members (Marinthe et al, 2020). In this set of studies, Marinthe et al showed that this increase in bias was due both to more positive evaluation of the ingroup and to devaluation of outgroups.…”
Section: Ingroup Symbol Desecration: a Threat To Social Identity Among Blind Patriotsmentioning
confidence: 97%